Assessing land use land cover changes in Langkawi island: towards sustainable urban living - Narimah Samat, (Environmental Management Society, Malaysia, 2010)
Simulating future urban growth might be useful in predicting the future urban fabric and its impact on the society, space and environment. This approach, however, needs to be undertaken with care such that it requires fundamental understanding of past and present situation. At present, urban area in developing nation is experiencing rapid urbanization and undergoing physical transformation, since majority of its population lives in urban area. It is therefore, essential that urban planners and managers understand the past and present land use land cover changes in order to predict its impacts on the society, economy and environment of the cities. This study aims to explore and assess land use land cover changes in Langkawi Island, Malaysia which has experienced significant increase of population during the last decade mainly due to the growth in tourism sector. The study monitored land use land cover changes since 1974 in order to assess the development of tourism activities and its impact on physical transformation of the island. Urban built-up area was controlled and directed towards existing built-up zone. However, annual urban expansion intensity index revealed that high speed of land use land cover transformation also occurred sporadically throughout the island especially after 1992 which might cause negative impact to the community